2017
DOI: 10.1097/qai.0000000000001549
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Consumption Directly Increases HIV Transmission Risk: A Randomized Controlled Experiment

Abstract: Background Alcohol consumption has frequently been purported as a driver of condomless sex and HIV transmission, but to date, experimental evidence for the causal risk-taking impact of alcohol among HIV-positive populations is lacking. The present experiment sought to determine whether acute alcohol consumption has a direct causal impact on condomless sex intentions among HIV-positive men-who-have-sex-with-men (MSM), and to assess whether alcohol's impact differs between MSM who are HIV-positive versus HIV-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 70 publications
(63 reference statements)
2
23
1
Order By: Relevance
“…As such, these results are most consistent with the interpretation that alcohol’s effects on CAS intentions among MSM are primarily accounted for by alcohol’s expectancy effects. These results contrast starkly with similar past studies conducted both among heterosexual men and women (16, 29) and among MSM (30, 32), since the majority of these studies did not find significant placebo effects on condomless sex intentions. Indeed, a meta-analysis of these studies, the majority of which were conducted among heterosexual men and women, found no differences between placebo and control conditions on condomless sex intentions (29).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As such, these results are most consistent with the interpretation that alcohol’s effects on CAS intentions among MSM are primarily accounted for by alcohol’s expectancy effects. These results contrast starkly with similar past studies conducted both among heterosexual men and women (16, 29) and among MSM (30, 32), since the majority of these studies did not find significant placebo effects on condomless sex intentions. Indeed, a meta-analysis of these studies, the majority of which were conducted among heterosexual men and women, found no differences between placebo and control conditions on condomless sex intentions (29).…”
Section: Discussioncontrasting
confidence: 99%
“…One possible explanation for our results could be that the placebo manipulations we used in this study might have been more effective than those in previous studies, and thus more effective in producing expectancy effects. However, this seems unlikely, given past studies show differences in perceived intoxication and the amount of alcohol consumed that are of similar magnitude as those reported here (30, 32). As such, our findings could suggest that alcohol’s expectancy effects on intentions may be stronger among MSM than previously understood.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…An experiment by Shuper et al 1 in Toronto was carried out to test the hypothesis that acute alcohol consumption would directly increase HIV-positive MSM’s intentions to engage in CLS. It also looked at whether impact of acute alcohol consumption on CLS intentions differed between HIV-positive and negative MSM.…”
Section: Acute Alcohol Consumption and Hiv Transmission Risk In Men Wmentioning
confidence: 99%